Proportion of Sewage Sludge to Soil Influences the Survival of Salmonella Dublin and Escherichia coli. Issue 4 (13th February 2018) - Ellis, Stephanie; Tyrrel, Sean; O'Leary, Emma; Richards, Karl; Griffiths, Bryan; Ritz, Karl
Abstract : The survival of enteric pathogens in sewage sludge can lead to their transferral into the soil environment and subsequent contamination of crops and water courses. This, in turn, can increase the potential spread of gastrointestinal disease. This work aims to determine the persistence of several microorganisms, co‐introduced with sewage sludge, when exposed to varying proportions of sewage sludge to soil. Three microcosm‐based studies are established, inoculated with Salmonella Dublin or an environmentally persistent strain of Escherichia coli (quantified periodically over a period of 42 days), or indigenous sewage sludge E. coli (quantified over a period of 56 days). Treatments consist of a mixture containing: 0, 15, 25, 50, 75, and 100% soil or sludge, depending upon the experiment. Each introduced microorganism decline significantly over time, with greater quantities of soil generally instigating greater die‐off particularly in the cases of environmentally persistent E. coli and S . Dublin. However, this relationship is not proportionally related as sludge/soil mixtures show greater declines than pure soil treatments. In contrast, indigenous sewage sludge E. coli has a more consistent decline across all treatments. This indicates that indigenous strains are more resilient and can be indicative of natural behavior. Moreover, the effects of soil‐borne factors on pathogen attenuation are context dependent and non‐linear, possibly arising from the relative spatial distribution of introduced sludge and attendant microbes in soil. Abstract : The persistence of pathogenic microorganisms co‐introduced with sewage sludge, when exposed to varying proportions of sewage sludge to soil, is determined. Introduced microorganisms decline significantly over time, with greater quantities of soil generally instigating greater die‐off, particularly in the cases of environmentally persistent Escherichia coli and Salmonella Dublin. However, this relationship is not directly proportionally related, as sludge/soil mixtures show greater declines than pure soil treatments.